(3YbhO NOeGJ GdeYdheGJ GdGdcJQhfjI aj GdbGfhf GdOhdj GdNGU (B/s - (3eMehO MhJg, YGOd GHhgTjeIs ((3GdbGgQI(B: s (3OGQ GdfgVI(B, s, 2004)
(3eGgjI YbO NOeGJ GdeYdheGJ GdOhdjI , JMOjO GdbGfhf GdhGLOH GdJWHjb Ydi YbhO NOeGJ GdeYdheGJ , GYeGd bGYOI bGfhf GdGQGOI aj YbhO NOeGJ GdeYdheGJ , JCKjQ GYJHGQGJ MeGjI GdeSJgdc Ydi JMOjO GdbGfhf GdhGLH GdJWHjb Ydi YbhO NOeGJ GdeYdheGJ JWHjb GdbhGYO GdehVhYjI ddJLGQI GdGdcJQhfjI Ydi YbhO NOeGJ GdeYdheGJ , fWGb GdbGfhf GdhGLH GdJWHjb Ydi YbhO NOeGJ GdeYdheGJ hHYV GdeTcdGJ GdeLGhQI , eTcdGJ Jchjf YbO NOeGJ GdeYdheGJ hCKGQg , GdeTcdGJ GdeQJHWI HYbhO NOeGJ GdeYdheJGJ , GdbVGA GdeNJU HaV efGRYGJ YbhO NOeGJ GdeYdheGJ (B.s
(3HjHdjhZQGajG (B: (3U(B. 320s
Keywords: (3GdYbhOs; (3GdbGfhf GdOhdj GdNGUs; (3GdeYdheGJs